12m+6n-6m+10n=

Simple and best practice solution for 12m+6n-6m+10n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12m+6n-6m+10n= equation:


Simplifying
12m + 6n + -6m + 10n = 0

Reorder the terms:
12m + -6m + 6n + 10n = 0

Combine like terms: 12m + -6m = 6m
6m + 6n + 10n = 0

Combine like terms: 6n + 10n = 16n
6m + 16n = 0

Solving
6m + 16n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-16n' to each side of the equation.
6m + 16n + -16n = 0 + -16n

Combine like terms: 16n + -16n = 0
6m + 0 = 0 + -16n
6m = 0 + -16n
Remove the zero:
6m = -16n

Divide each side by '6'.
m = -2.666666667n

Simplifying
m = -2.666666667n

See similar equations:

| 10m+12-4m-19=m-3+4m-4 | | (3x+y^2+2y^5)dx+(2x^2y+5xy^4)dy=0 | | x^2-12i=5 | | 7+9d-4-4d=5d+3-d+8 | | 10x-5+2=7x+21 | | -2(2x+3)-4=-7 | | 5j*6y= | | 3x+y-15=0 | | 4y+5y=6 | | -8t+16=7(10-8t) | | 10+3x-2+x=3x+6+2x+8 | | -15-2(-3y+5)=10 | | 5x+8-3x-11=3x-5 | | 4(3t-2)=5(2t+3) | | 10h-29=51 | | 2(-3y+5)+15=10 | | 25-30+9x=6x-20 | | 1/3(4x-44)=5x | | (n-1)(n-2)(n-3)(n-4)(n-5)(n-6)(n-7)=0 | | (2+n)(n-1)(n-2)(n-3)(n-4)(n-5)(n-6)=0 | | x^2-y^2=623 | | (3+n)(2+n)(n-1)(n-2)(n-3)(n-4)(n-5)=0 | | 5x^3+5=0 | | (4+n)(3+n)(2+n)(n-1)(n-2)(n-3)(n-4)=0 | | (5+n)(4+n)(3+n)(2+n)(n-1)(n-2)(n-3)=0 | | (6+n)(5+n)(4+n)(3+n)(2+n)(n-1)(n-2)=0 | | (7+n)(6+n)(5+n)(4+n)(3+n)(2+n)(n-1)=0 | | -16t^2+24t+4=0 | | (8+n)(7+n)(6+n)(5+n)(4+n)(3+n)(2+n)=0 | | 8x^2-7x-38=x | | 7-2p=6p-9 | | 2y+10x=400 |

Equations solver categories